Calcium plus vitamin D supplementation and lung cancer incidence among postmenopausal women in the Women's Health Initiative. (August 2017) - Tao, Meng-Hua; Dai, Qi; Chen, Shande; Freudenheim, Jo L.; Rohan, Thomas; Wakelee, Heather; Datta, Mridul; Wactawski-Wende, Jean
Highlights: The effect of calcium and vitamin D supplementation on lung cancer was evaluated. There was no difference in lung cancer incidence between randomization groups. An interaction between baseline Ca:Mg ratio and supplementation in current smokers. Abstract: Background: Magnesium and calcium are antagonistic in many physiologic processes. However, few studies have investigated the associations of supplemental calcium with lung cancer risk taking this antagonism into account. We evaluated the effect of calcium and vitamin D supplementation on lung cancer incidence and explored whether the ratio of baseline calcium to magnesium (Ca:Mg) intake modifies the association in the Women's Health Initiative (WHI) calcium plus vitamin D supplementation (CaD) trial. Methods: The intervention phase of the WHI CaD was a double-blinded, randomized, placebo-controlled trial in 36, 382 postmenopausal women aged 50–79 years, recruited at 40 U.S. centers. Post-intervention follow-up continued among 29, 862 (86%) of the surviving participants. Risk of lung cancer in association with CaD supplementation was evaluated using proportional hazard regression models. Results: After 11 years' cumulative follow-up, there were 207 lung cancers (incidence 0.11% per year) in the supplement arm and 241 (0.12%) in the placebo arm (hazard ratio (HR) for the intervention, 0.91; 95% confidence interval (CI), 0.71–1.17). Subgroup analyses suggested that the HR for lung cancer varied by baseline Ca:Mg intake ratio among women who were current smokers at enrollment ( p = 0.04 for interaction). Conclusions: Over the entire follow-up period, calcium and vitamin D supplementation did not reduce lung cancer incidence among postmenopausal women. In exploratory analyses, an interaction was found for the baseline Ca:Mg intake ratio on lung cancer among current smokers at the trial entry. This findings need to be further studied for the role of calcium with magnesium in lung carcinogenesis in current smokers.